2006
DOI: 10.1007/s00244-005-0016-9
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of HCHs and DDTs in Soils from Beijing City, China

Abstract: Abstract. Concentrations of HCH isomers, DDT, and its metabolites have been measured in 63 soil samples collected in the urban area and outskirts of Beijing City. HCHs and DDTs were observed in all samples and their geometric mean levels were 5.78 and 38.21 ng g)1, respectively. The spatial distribution of OCPs in Beijing was clearly showed by the contour map, suggesting the sites with the higher level of OCPs are located in the west and the south region and urban areas within the study regions.ÕÕ Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 34 publications
3
28
1
Order By: Relevance
“…Although the residue levels of DDT and HCH were different in the soils, a significant positive correlation was observed between P HCH and P DDT (p \ 0.01). This correlation probably showed that both HCHs and DDTs had similar sources and fate in the study area (Li et al 2006b). There were no significant correlations between DDT concentrations and TOC content, which indicated that the residue levels were a reflection of DDTs application history and dissipation rates rather than air-soil equilibrium, which is similar to agricultural soils from Alabama, USA (Harner et al 1999) and different from the surface soils from Tianjin, China ).…”
Section: Resultsmentioning
confidence: 69%
“…Although the residue levels of DDT and HCH were different in the soils, a significant positive correlation was observed between P HCH and P DDT (p \ 0.01). This correlation probably showed that both HCHs and DDTs had similar sources and fate in the study area (Li et al 2006b). There were no significant correlations between DDT concentrations and TOC content, which indicated that the residue levels were a reflection of DDTs application history and dissipation rates rather than air-soil equilibrium, which is similar to agricultural soils from Alabama, USA (Harner et al 1999) and different from the surface soils from Tianjin, China ).…”
Section: Resultsmentioning
confidence: 69%
“…Therefore, the correlations probably indicate that DDTs, HCHs and HCB have some similar sources within the study area. The studies of OCPs in remote Austrian forest soils (Weiss et al 2000) and Beijing urban soils (Li et al 2006c) drew similar conclusions. The concentrations of γ-HCH had no correlation with ΣDDT concentrations.…”
Section: Correlations Between Individual Compoundsmentioning
confidence: 55%
“…In comparison with other areas of China, the median value (1.768 ng g À1 ) was slightly higher than that in soils from the Guanting Reservoir, which is located in an exturb of Beijing with fewer anthropogenic activities (median: 0.56 ng g À1 , Zhang et al, 2005). However, the geometric mean was 2-8 times lower than that in soils from the urban and suburban areas of Beijing determined via a systematic grid sampling method (geometric mean: 5.7 ng g À1 , Li et al, 2006) and that in agricultural soils from greenhouses in suburban areas of Beijing (15.77 ± 6.0 ng g À1 , Ma et al, 2003). It was also obviously much lower than that in rice soil from Jiaxing, a famous agricultural area in China (18.6-55.4 ng g À1 , Zhao et al, 2002) and that in Tianjin, a city adjacent to Beijing with recent production and usage of HCHs (45.8 ng g À1 , Gong et al, 2004a).…”
Section: Hchsmentioning
confidence: 74%
“…Numerous studies have indicated that toxic trace pollutants might reach concentrations of concern to human health in urban environments (Evans et al, 1992;Mielke et al, 1999;De Kimple and Morel, 2000;Chen et al, 2005;Li et al, 2006;Tulve et al, 2006). In contrast to agricultural soils, urban soils might have a direct influence on public health since pollutants in the soils can easily be transferred into humans via ingestion, inhalation, or dermal routes, etc.…”
Section: Introductionmentioning
confidence: 99%